Numerical Solution of Fourth-order Initial Value Problems Using Novel Fourth-order Block Algorithm - Akinnukawe, Blessing Iziegbe; Kuboye, John Olusola; Okunuga, Solomon Adewale (Journal of Nepal Mathematical Society, 2024)
In this paper, a one-step fourth-order block scheme for solving fourth order Initial Value Problems (IVPs) of Ordinary Differential Equations (ODE) is developed using interpolation and collocation techniques. The derived schemes contain two hybrid points which are chosen such that 0 < w1 < w2 < 1 where w1 and w2 are defined as hybrid points. The characteristics of the developed schemes are analyzed. The obtained schemes are applied in block form to solve some fourth-order IVPs and the numerical results show the accuracy and effectiveness of the block scheme compared with some existing methods.